Oh, the places they'll go! A survey of phytopathogen effectors and their host targets. (25th December 2017) - Khan, Madiha; Seto, Derek; Subramaniam, Rajagopal; Desveaux, Darrell
Summary: Phytopathogens translocate effector proteins into plant cells where they sabotage the host cellular machinery to promote infection. An individual pathogen can translocate numerous distinct effectors during the infection process to target an array of host macromolecules (proteins, metabolites, DNA, etc.) and manipulate them using a variety of enzymatic activities. In this review, we have surveyed the literature for effector targets and curated them to convey the range of functions carried out by phytopathogenic proteins inside host cells. In particular, we have curated the locations of effector targets, as well as their biological and molecular functions and compared these properties across diverse phytopathogens. This analysis validates previous observations about effector functions (e.g. immunosuppression), and also highlights some interesting features regarding effector specificity as well as functional diversification of phytopathogen virulence strategies. Significance Statement: Phytopathogenic effectors play deterministic roles in the outcome of plant‐pathogen interactions. We have surveyed the literature for effector targets and curated them to provide a comparative overview of effector biology as well as insights into phytopathogen virulence strategies.